The mechanism of dislocation multiplication during thermally induced γ ↔ ε transformations in the Fe-17Mn alloy. (1st March 2023) - Hong, Jin-Sung; Lee, Young-Kook
Abstract: In the present study, the mechanism of dislocation multiplication occurring during thermally-induced γ austenite ↔ ε martensite transformation in the Fe-17Mn alloy was investigated using an in-situ transmission electron microscope. Dislocations were introduced in γ at grain boundaries and inside the grains during thermally-induced γ ↔ ε transformations. Dislocations near grain boundaries were the dislocations, which constituted ε martensite and returned to grain boundaries during ε → γ reverse transformation, and forest dislocations introduced by plastic deformation occurring during γ ↔ ε transformations. Dislocations, which formed by the impingement between two ε platelets and by the branching of a new ε platelet from a preexisting ε platelet, remained inside the γ grain during ε → γ reverse transformation. Graphical abstract: Image, graphical abstract